PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR PADA MATERI KESEBANGUNAN DI KELAS VII SMP NEGERI 22 SAMARINDA - Firanda, Firanda; Berahman, Berahman; Widyasari, Tri; Haeruddin, Haeruddin (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2025)
Mathematics learning is a process of building mathematical knowledge by teachers to students. However, the learning outcomes obtained are still relatively lacking, especially in SMP Negeri 22 Samarinda. The purpose of this study was to determine whether or not there was an influence of the Discovery Learning learning model on learning outcomes in the similarity material in class VII of SMP Negeri 22 Samarinda. This study used a quasi-experimental method with a posttest-only control group design. The population of this study was all students of class VII of SMP Negeri 22 Samarinda as many as 325 students divided into 11 classes. The sampling technique used a purposive sampling technique. The sample of this study was class F as an experimental class of 35 students who applied the Discovery Learning learning model and class E as a control class of 36 students who applied the Conventional learning model. Data analysis used descriptive statistics and inferential statistics. The results of the descriptive statistical analysis showed that the average learning outcomes of the experimental class were 55.886, while the control class was 41.056. The results of the inferential analysis using the Independent Sample t-Test with right-hand testing showed a statistical significance value <the test significance value, which was 0.001 <0.05 so that H_0 was rejected. Based on the results of the analysis, it was concluded that there was an influence of the Discovery Learning learning model on learning outcomes in the similarity material in class VII of SMP Negeri 22 Samarinda.